Productivity measurement: racing to keep up - Sichel, Daniel E. (Cambridge, MA, 2019)
"This paper provides a non-technical review of the literature and issues related to the measurement of aggregate productivity. I begin with a discussion of productivity measures, their performance in recent decades, and key measurement puzzles that emerge from the data. The remainder of the review focuses on two important questions. First, how do we make more accurate the measures of prices used to deflate nominal output so as to win (or at least not lose) the race for economic measurement to keep up with a changing economy? This section frames the issues and points to the most important and promising areas for further research. Second, what does or should GDP measure? I defend GDP as a valuable measure of production and offer suggestions for improving it. At the same time, I emphasize the importance of measuring economic welfare (well being) and highlight the value of supplementing GDP with a satellite account that measures economic welfare."